Comments on: nonlinear wind-drift ocean currents in arctic regions. Issue 2 (4th March 2022) - Constantin, Adrian
ABSTRACT: We clarify and correct an oversight from a recent paper, thus confirming the possibility of a nonlinear coupling of inertial oscillations and Ekman-type spiralling wind-drift currents to yield an exact solution of the system describing the leading-order dynamics of wind-drift arctic flows.